Coffee Breeding in Kenya: Achievements, Challenges and Current Focus - Gichimu, Bernard M. (My University, 2015)
Coffee production in Kenya is seriously constrained by two fungal diseases namely Coffee Berry Disease (CBD) caused by Colletotrichum kahawae (Waller & Bridge) and Coffee Leaf Rust (CLR) caused by Hemileia vastatrix (Berk. and Br.). Growing resistant varieties is believed to be the most cost effective and sustainable means of managing plant diseases. In Kenya considerable success has been made in coffee breeding to improve yields, quality and to manage the two economically important diseases. However, emerging issues such as climate change have brought up new challenges which require to be addressed to ensure sustainability in coffee production. This paper reviews some of the achievements, challenges and future prospects/approaches to develop cost effective and sustainable coffee varieties that enhance yield and quality.